Comprehensive, School‐Based Preventive Dentistry: Program Details and Students' Unmet Dental Needs. (13th August 2021) - Aldosari, Muath A.; Bukhari, Omair M.; Ruff, Ryan Richard; Palmisano, Joseph N.; Nguyen, Helen; Douglass, Chester W.; Niederman, Richard; Starr, Jacqueline R.
ABSTRACT: BACKGROUND: In this paper, we describe the design, program details, and baseline demographics and oral health of participants in ForsythKids, a regional, comprehensive, school‐based mobile caries prevention program. METHODS: We solicited all Massachusetts elementary schools with greater than 50% of students receiving free or reduced‐price meals. Six schools initially elected to participate, ultimately followed by over 50 schools. Interventions were based on systematic reviews and randomized controlled caries prevention trials. Participating students received semiannual dental examinations, followed by comprehensive preventive care. Summary statistics regarding oral health indicators were derived from individual tooth‐ and surface‐level data. RESULTS: Over a 6‐year period, data were collected on 6927 children. The number of students per school ranged from 58 to 681. The overall participation rate was 15%, ranging from 10% to 29%. Overall, 57% of the children were younger than 8 years at baseline. Approximately, 54% of children experienced dental decay on any tooth at baseline; 32% had untreated decay on any tooth, 29% had untreated decay on primary teeth, and 10% untreated decay on permanent teeth. CONCLUSIONS: Untreated dental decay was double the national average, even in schools within several blocks of community dental clinics. These data demonstrate the need for caries prevention beyond the traditional dental practice.